Al 'Adah Muhakkamah Rules and Their Applications Regarding the Contemporary Era Share Purchase and Sale Agreement - Muhamad Iqbal Akbar; Mohamad Fikri bin Mohd Bakri (Yayasan Adra Karima Hubbi, 2024)
The principles of